Uji kinerja mesin pemecah kulit kemiri tipe impact rotary - Fahrizal Fahrizal; Sealtial Mau; Damianus Manesi; Tri Mandala Putra (TURBO [Tulisan Riset Berbasis Online], 2026)
An impact rotary–type candlenut shelling machine utilizes centrifugal force to strike candlenuts that fall by gravity, projecting them outward to collide with the chamber wall. This method is expected to provide higher shelling efficiency than existing techniques. This study aimed to examine the effect of blades rotational speed on shelling efficiency. An experimental approach with a randomized design was employed, using rotational speed as a single factor with four levels: 850, 980, 1140, and 1300 rpm. Candlenuts were obtained from farmers in Amarasi District, Kupang Regency. The candlenuts were dried in the sun for 5 days before testing. Data collection was carried out by testing a shelling machine according to the experimental design. The results of the study found that the higher the rotation speed of the blades, the higher of capacity. Shelling efficiency was evaluated by measuring the weight of shelled candlenuts from each treatment. The results of the study found that the higher the rotation speed, the higher the capacity. However, the highest shelling efficiency was achieved at 850 rpm, the lowest effective speed. At this speed, the output consisted of 33.03% whole kernels, 30.33% semi-broken kernels, 15.9% crushed kernels, and 20.74% kernels with adhering shell fragments.